Enhanced discriminative stimulus effects of Δ9-THC in the presence of cannabidiol and 8-OH-DPAT in rhesus monkeys. (1st August 2016) - McMahon, Lance R.
Highlights: Cannabidiol lacks CB1 receptor agonist or antagonist activity in primates. Cannabidiol amounts larger than those in Cannabis or nabiximols enhance Δ 9 -THC. Cannabidiol and a 5-HT1A receptor agonist have overlapping behavioral effects. 5-HT1A agonism enhances the CB1 receptor-mediated effects of Δ 9 -THC. Abstract: Background: Cannabidiol, a therapeutic with potential serotonin (5-hydroxytryptamine; 5-HT) 5-HT1A receptor agonist activity, is the second most prevalent cannabinoid in Cannabis after Δ 9 -THC. The extent to which cannabidiol modifies the effects of Δ 9 -THC has not been firmly established, especially with respect to abuse-related effects in rhesus monkeys where previously antagonistic interactions have been reported for some behavioral outcomes. Methods: Cannabidiol and the 5-HT1A receptor agonist (±)-8-hydroxy-2-(dipropylamino)tetralin hydrobromide (8-OH-DPAT) were tested in two separate discrimination assays in rhesus monkeys. One group (n = 6) discriminated Δ 9 -tetrahydrocannabinol (Δ 9 -THC; 0.1 mg/kg i.v.); a second group (n = 6) discriminated the cannabinoid antagonist rimonabant (1 mg/kg i.v.) while receiving Δ 9 -THC daily (1 mg/kg/12 h s.c.). Responding was maintained under a fixed ratio 5 schedule of stimulus-shock termination. Results: Both training drugs dose-dependently increased the percentage of responses on the respective drug-associated levers. Cannabidiol (up to 17.8 mg/kg) and 8-OH-DPAT (up to 0.178 mg/kg) did not substitute for either training drug; however, both significantly increased the potency of Δ 9 -THC to produce discriminative stimulus effects. Moreover, 8-OH-DPAT significantly attenuated the discriminative stimulus effects of rimonabant, whereas cannabidiol did not modify the rimonabant discriminative stimulus. Conclusions: These results, which are consistent with cannabidiol lacking CB1 receptor agonist or antagonist activity in vivo, demonstrate enhancement of the effects of Δ 9 -THC by cannabidiol, albeit at cannabidiol amounts larger than those in Cannabis or cannabidiol-based therapeutics (nabiximols). In addition to showing that cannabidiol and a 5-HT1A receptor agonist have overlapping behavioral effects, the current results suggest that 5-HT1A agonism enhances the CB1 receptor-mediated effects of Δ 9 -THC.